NLRP3 augmented resistance to gemcitabine in triple-negative breast cancer cells via EMT/IL-1β/Wnt/β-catenin signaling pathway. Issue 7 (3rd July 2020) - Zheng, Qiao; Yao, Dejiao; Cai, Yi; Zhou, Tiecheng
Abstract: Background: Gemcitabine is widely used in the treatment of breast cancer (BC). However, the resistance to drugs remains a tough concern. The study explored the potential mechanism concerning gemcitabine resistance in triple-negative BC (TNBC) in vitro . Methods: TNBC cells (TNBCC) and gemcitabine-resistance cell lines (GRC) were used. We investigated the sensitivity to gemcitabine responsive to regulation of Nod-like receptor protein 3 (NLRP3) expression in TNBCC in different gemcitabine concentrations. RT-PCR checked NLRP3 mRNA expression and MTT assessed the cell cytotoxicity. Gemcitabine resistance was studied in GRC exposed to 0, 1, 3, 5 nm gemcitabine after GRC were treated with NLRP3 agonist Nigericin sodium salt (NSS) or antagonist CY-09. Epithelial-to-mesenchymal transition (EMT) biomarkers were evaluated via RT-PCR and inflammasome IL-1β, β-catenin content and GSK-3β activity were measured by ELISA methods. Last, we inactivated the signaling and examined the NLRP3, EMT mRNA expression by RT-PCR, IL-1β, β-catenin content and GSK-3β activity by ELISA and cell cytotoxicity through MTT. Results: NLRP3 up-regulation improved cell survival and reduced sensitivity to gemcitabine ( P <0.05). NLRP3 had higher expression in GRC than TNBCC. GRC cell viability dropped as the gemcitabine concentration increased. NLRP3 up-regulation added to resistance to gemcitabine in GRC ( P <0.05). NLRP3 agonist might induce EMT process, activate wnt/β-catenin signaling and IL-1β, while inactivation of wnt/β-catenin signaling could result in the inhibition of NLRP3, IL-1β and EMT as well as cell viability in GRC ( P <0.05). Conclusion: NLRP3 could enhance resistance to gemcitabine via IL-1β/EMT/Wnt/β-catenin signaling, which suggested that NLRP3 antagonist CY-09 might be incorporated into gemcitabine treatment for TNBC.